The Impact of Information and Communication Technology (ICT) on Intra-Arab Trade: The Case of the Gulf Cooperation Council - Kofahi, Mohammed; Warrad, Taleb (Jordan Journal of Economic Sciences, 2020)
This study aims at measuring the impact of information and communication technology (ICT) on intra-Gulf Cooperation Council (GCC) trade. The Augmented Gravity Model was used to conduct the standard analysis on panel data covering the period from 2005 to 2016. The FGLS: Feasible Generalized Least Squares method was used to analyze and test the relationship between trade flows (exports) and ICT. The percentage of subscriptions of landlines in both the exporting and importing countries and the percentage of broadband subscriptions in the exporting country only has a significant positive effect on the volume of regional trade in the GCC countries, while the percentage of broadband subscriptions in the importing country doesn’t have a significant effect. As for the other explanatory factors of the gravity model, it has turned out that, GDP and population have a significant positive effect on the volume of intra trade in the GCC countries, while the distance has a negative significant effect. These results are consistent with the theoretical framework of the gravity model.